PENGARUH PENDIDIKAN KESEHATAN PERTOLONGAN PERTAMA PADA KECELAKAAN (P3K) TERHADAP TINGKAT PENGETAHUAN ANGGOTA SAKA BAKTI HUSADA - Endiyono Endiyono; Sinta Aprianingsih (Universitas Respati Yogyakarta, 2020)
Background: Accident is one of the unintended, unexpected happenings that can cause injury and even loss of life. Providing health education on first aid on accidents will increase knowledge to give proper help which will reduce disability or suffering and even save the victim from death.Objective: To reveal the effect of health education to First Aid to the level of knowledge of Saka Bakti Husada.Methods: This research applied quantitative method with pre-experimental design with one group pre and post-test without control group design. Population and sample consisted of 40 persons with total sampling technique. Wilcoxon test was applied to analyze the data.Results: The average score of knowledge level before receiving the health education in good category was 11 respondents (27.5%), after getting health education was 39 respondents (97.5%). The mean of respondents knowledge beforeand after health education was 1.78 and 2.98. The result of Wilcoxon Signed Rank Test obtained Z score -5.665 and p value = 0,000, H0 was rejected if p < 0.05, it means that there is a difference of knowledge of respondents before and after health education first aid on accidents.Conclusion: First aid health education on accidents can be affect the level of knowledge of Saka Bakti